Cultivating the Language Skills of Elementary School Students: Effective and Enjoyable Learning Styles and Strategies - Nursalim Nursalim; Ahmad Syarief; Fuji Rahayu; Tiara Trirahmayati (Jurnal Inovasi Pendidikan dan Sains, 2025)
Good language skills in elementary school children are an important factor in their academic and social development. This study aims to analyze effective and enjoyable learning styles and strategies in cultivating the language skills of elementary school students. The method used is qualitative research with a case study approach, involving five teachers and ten students as participants. Data collection techniques were carried out through interviews, observations, and document analysis. The results of the study show that learning styles and strategies based on language games, the use of picture story media, project-based literacy approaches, as well as interactive and collaborative methods contribute positively to the improvement of students’ language skills. In line with the indicators, students who were involved in language game-based learning showed improvement in vocabulary and speaking skills, while the use of picture storybooks helped enhance reading comprehension. The project-based literacy approach, such as daily journal writing, was also proven to improve students’ writing skills. However, the implementation of these strategies involves limitations in learning facilities, differences in students’ ability levels, and limited instructional time. This study recommends strengthening the variety of learning strategies, improving literacy facilities, and providing support from both the school and parents to create a more conducive learning environment. Through the implementation of innovative and experience-based methods, language learning at the elementary school level can become more engaging and effective for students